2015
DOI: 10.1177/0021998315597989
|View full text |Cite
|
Sign up to set email alerts
|

In-plane and through-thickness permeability models for three-dimensional Interlock fabrics

Abstract: An analytical model has been created to estimate the in-plane and through-thickness permeability of three-dimensional Interlock fabrics. The model is based on the calculation of the pressure drop in the mesoscopic pores, i.e. in the inter-tow spaces of the fabric. Firstly, the dimensions and distribution of the mesopores are determined from the weaving parameters. A mesoscopic permeability model can then be inferred from the fabric structural data. The contribution of the microscopic flow inside the tows is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Carbon plain weave reinforcement presents a lower diameter, which contributes to fiber packaging and difficult flow path and generating more voids. 40 In addition, the impregnation difficulty is responsible for defects in the laminates, mainly near laminate end of the composite (red circles). These defects presented attenuation between 80% and 100%, associated to macroscopic voids and other defects, e.g.…”
Section: Processing Resultsmentioning
confidence: 99%
“…Carbon plain weave reinforcement presents a lower diameter, which contributes to fiber packaging and difficult flow path and generating more voids. 40 In addition, the impregnation difficulty is responsible for defects in the laminates, mainly near laminate end of the composite (red circles). These defects presented attenuation between 80% and 100%, associated to macroscopic voids and other defects, e.g.…”
Section: Processing Resultsmentioning
confidence: 99%
“…Based on the finite element model of this literature [17,18,20], the 2.5D woven preform was regarded as a porous material with a definite geometry. The flow of resin in the fabric unit cell consisted of the micro-flow of resin in the interior of yarn and the meso-flow between the yarns, as depicted in Figure 6a.…”
Section: Resultsmentioning
confidence: 99%
“…Chen [14] used a dual-scale model to predict the fabric permeability, and the results showed that the permeabilities of fabrics with the same fiber volume fractions were not necessarily the same. Investigators [15,16,17,18] have established theoretical models to predict the permeabilities of three-dimensional orthogonal and angle-interlock woven fabrics and provided experimental validation of these models. However, the effect of shear deformation on the fabric permeability was not considered in the studies mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The permeability of 3D fabrics was widely investigated in recent years. [10][11][12][13] In a previous work, 14 an analytical model was elaborated to predict the in-plane and through-thickness permeability of 3D interlock fabrics. The first part of this model predicts the average inter-tow mesoscopic pore dimensions such as their height, width, and length along a cross section, and the pore distribution along the warp, weft, and through-thickness directions of five different reinforcements.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the present study is to investigate experimentally the mesoscopic pore size and distribution for the five 3D interlock fabrics considered in order to provide accurate input data to complete the validation of the model developed in Vernet and Trochu. 14 To achieve this goal, our investigation is divided in two main stages: (1) the experimental analysis of the pore dimensions; and (2) the application of the second part of the model developed in Vernet and Trochu 14 using the experimentally observed pore dimensions instead of the analytical predictions.…”
Section: Introductionmentioning
confidence: 99%